AN ASSESSMENT ON THE EFFECTIVENESS OF CORAL REEF MANAGEMENT BY TOURISM SECTOR IN NHA TRANG BAY, VIETNAM - Tuan, Vo Si; Tuyen, Hua Thai; Long, Nguyen Van; Hoang, Phan Kim; Ben, Hoang Xuan; Dat, Mai Xuan (Vietnam Journal of Marine Science and Technology, 2019)
The models of coral reef management for the development of ecological tourism were conducted under the coordination among the 3 businesses (Khanh Hoa Salanganes Nest Company, Vinpearl Nha Trang and Tri Nguyen Tourism), Institute of Oceanography and Khanh Hoa Department of Natural Resources & Environment. The analysis of trends of coral cover, density of reef fishes and big size invertebrates at 3 sites allowed assessing effectiveness of 3 years’ management. The stability of hard coral cover, except the decline at southern Hon Tam due to impacts of the typhoon in Nov., 2017 indicated no increased damage to corals from human activities. However, the dominance of small size fish (< 10 cm in length), the decline of density of larger size fish and the poorness of large size invertebrate showed continuous overexploitation at these managed areas.